Configuration space–based discrete event system specification formalism for a smart factory with real-time flexibility - Chang, Dae S.; Park, Sang C. (Concurrent Engineering Research and Applications, 2018)
A manufacturing system consists of various manufacturing devices, and each device has a set of tasks which are triggered by specific commands. Traditionally, simulation has been considered as an essential technology for the evaluation and analysis of manufacturing systems. Although discrete event system specification formalism has been a popular modeling tool for manufacturing systems, it has limitations in describing situations such as sudden cancelation of tasks. Proposed in this article is an extended discrete event system specification formalism for the effective description of a smart factory which requires the intelligence to handle turbulences in real-time production. The extended discrete event system specification formalism incorporates the configuration space concept, which is well-known in classical mechanics. While the conventional discrete event system specification formalism uses only the logical states set to represent the device states, the proposed formalism employs the combination of two sets: a logical states set (sequential states set) and a physical states set (configuration space of the device). As a result, the extended formalism enables the effective description of nondeterministic tasks which may occur frequently in a smart factory.
Keywords: Classical mechanics; Configuration space; Discrete event system specification; Evaluation and analysis; Manufacturing devices; Real time; Real-time production; Simulation model; configuration space; discrete event system specification formalism; real-time flexibility; simulation model; smart factory